Robot navigation based on building information model (BIM) - Loh, Bao Wei (Nanyang Technological University, 2021)
The construction industry plays a great part in Singapore. Hence, it is very important that the construction industry continuously improves itself in terms of productivity and accuracy. There have been various technological implementations which has helped the construction industry to do so, and such emerging applications includes the usage of Building Information Model (BIM) and robotics. In this project, ROS will be utilised alongside with a BIM software, Revit, to enable the usage of robotics to assist in the checking of installation. To do so, the user will select the target installation, for example a window or door, in the 3D model of the floorplan in Revit. Dynamo, a visual programming software embedded in Revit, will be used to process the coordinates and dimensions of the selected installation. These will be transferred to the ROS system via cloud. Thereafter, the ROS side will retrieve these information to generate the navigation goal for the robot. The robot will then go to the navigation goal and capture the image. A Simultaneous Localisation and Mapping (SLAM) algorithm will be implemented to generate the map of the actual environment. Two types of robots – Aliengo by Unitree Robotics and Scout by Weston Robots – will be used in this project.